Meningkatkan Perkembangan Bahasa Anak Melalui Metode Bercerita Dengan Media Audio Visual Di Kelas A RA Nurul Ilmi Samboja - Yenik Wahyuningsih; Mutiah Wati (Al Tahdzib: Jurnal Pendidikan Islam Anak Usia Dini, 2023)
The aim of the research was to find out how to improve language development by storytelling using audio-visual media and the use of audio-visual media to improve language development through storytelling in Class A Nurul Ilmi, Samboja District. This type of research is class action which is carried out in two cycles, each cycle is carried out with the stages of planning, action, observation and reflection. The results of the study: aspects of receiving language before being given action 54%. Then in the first cycle there was an increase of about 77%, in the second cycle there was an increase of 85%. In the final stage: children can understand simple commands by 92%, can repeat more complex sentences by 100%, can mention some adjectives by 92%, can answer more complex questions by 92%, can tell causal events by 77 %, can name objects around 92%, can say letter symbols by 77%, knows initial syllables by 85%, can read own name by 85%, can connect pictures of objects with words by 100%, knows symbols can write letters by 92%, understanding between sounds and shapes by 85%, being able to write own name by 92%, being able to draw freely by 100%.